ANALISIS KONTRIBUSI, EFISIENSI DAN EFEKTIVITAS JASA TRANSPORTASI DAN PERGUDANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU: ANALISIS KONTRIBUSI, EFISIENSI DAN EFEKTIVITAS JASA TRANSPORTASI DAN PERGUDANGAN TERHADAP PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DI KABUPATEN BERAU - Winda Jubaedah (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2021)
The purpose of this research is to determine the contribution of the education service sector to the gross regional domestic product in Berau Regency, so that it can assist the Berau Regency government ini making programs and policies in the future.In this study using secondary data or publication data obtained from the Central Bureau of statistics of Berau Regency using data analysis, namely contribution analysis. With data for the 2015-2019 period of Berau Regency.Based on the results of the research and the results of the contribution data, it is concluded that the transportation and warehousing service sector has a very low contribution to the growth of Gross Regional Domestic Product when viewed with the contribution indicator. Based on the results of the table, it can be concluded that the level of effectiveness for 5 years is still far below 60% which is categorized as ineffective.